Increasing health awareness for the community of Mushola Al-Mubarokah at Medang Lestari Housing, Tangerang - Ischak, Mohammad (Community Empowerment, 2021)
The government has handled the Covid-19 pandemic with massive programs and policies and involved all levels of society. Likewise, the socialization of health protocols in order to control and reduce the impact of the pandemic. Nevertheless, nowadays, often people ignore the protocol. One of the strategic components of society in order to socialize as well as implement health protocols is the community of worshipers which is coordinated by the Mushola Prosperity Council (DKM). This community service is carried out with the rationale of the effectiveness of the socialization of the application of health protocols, especially in worship activities, to the community of Mushola Al-Mubarokah, RW 09, Medang Lestari, Tangerang. The method is socialization that utilizes the DKM routine activities such as recitations and management meetings. This effort succeeded in instilling discipline in the community and DKM administrators to maintain and discipline the community to voluntarily implement health protocols in routine activities, while other mosques relaxing the implementation of health protocols.